Developing workplace research skills to bridge the innovation gap between University and Industry - Hamburg, Ileana; Vladut, Gabriel (Advances in Social Sciences Research Journal, 2019)
Cooperation between university and industry/business for innovation and education is important particularly due to uncertainty in economies, increase competitive global markets and low growing prospects. There is necessaryto look what are most important topics that, practitioners, policymakers and researchers need to advance in the next years, why these topics are important and which approaches are needed to address these topics.In this paper one of such topics is addressed within cooperation with Small and medium sized companies (SMEs) which are drivers of Europe’s economycompanies.This paper will explore how to enhance the ability of SMEs to become more innovative by exploiting researchskills and knowledge being created in third level institutes.